Dietary alfalfa improved growth performance, survival, body and fatty acid composition, flesh quality and immune-antioxidant system in Pacific white shrimp (Litopenaeus vannamei) - Kobra Babanejad-Abkenar; Arash Akbarzadeh; Ahmad Noori; Mohammad Niroomand (Aquaculture Reports)
Alfalfa is a suitable food item in the diet of aquaculture species, offering valuable nutritional components, cost-effectiveness, widespread availability, and sustainable production practices. This study investigated the effects of dietary alfalfa leaf powder (ALP) on growth performance, survival, body and fatty acid composition, astaxanthin content, flesh quality, and the immune-antioxidant system of Pacific white shrimp (Litopenaeus vannamei). A total of 1050 healthy shrimp with an initial mean weight of 7.58 ± 0.10 g were fed diets containing 0 (control), 60 (ALP60), 120 (ALP120), and 180 (ALP180) g/kg of ALP for eight weeks. Results showed significantly improved growth indices in the ALP60 treatment compared to the control group (p < 0.05). Additionally, all ALP-fed shrimp showed significantly higher survival rates compared to the control group (p < 0.05). The highest carcass protein and lowest lipid levels were observed in the ALP180 treatment. The fatty acid composition showed that C14:0 levels were lower in all ALP treatments compared to the control, while ALP120 and ALP180 treatments had higher ALA, total (n-6) fatty acids, and EPA levels compared to the control group (p < 0.05). It also increased astaxanthin levels, meat quality (redness index), and the activity of immune antioxidant enzymes (superoxide dismutase, glutathione peroxidase, and lysozyme), especially in ALP120 and ALP180 treatments. Furthermore, ALP supplementation reduced hemolymph cholesterol and glucose levels. Overall, this study demonstrates that dietary ALP positively influences growth, survival, body composition, astaxanthin content, flesh quality, and immune function in shrimp, highlighting its potential to improve shrimp health and quality.